The Effect of Implementing Group Counseling Services with the Behavior Contract Technique on Academic Procrastination and Increasing Learning Motivation at State Vocational High School 1 Kotabumi, North Lampung - Arfani Fernando Fahmi; Sutarto Sutarto; Sumarto Sumarto; Dina Hajja Ristianti; Dewi Purnama Sari (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Academic procrastination and low learning motivation can hinder students’ achievement. This study aims to determine the effect of group counseling services using the behavior contract technique on reducing academic procrastination and increasing learning motivation. The research employed a quasi-experimental design with purposive sampling, involving two eleventh-grade classes (around 60 students) divided into experimental and control groups. Instruments used were academic procrastination and learning motivation questionnaires with a Likert scale, analyzed using MANOVA. The results showed that group counseling with the behavior contract technique had a significant effect in reducing procrastination and increasing learning motivation. In the experimental group, the average procrastination score decreased from 98.3 to 52.8, while learning motivation increased from 44.3 to 101.2. The MANOVA test showed a significance value of 0.000 < 0.05, indicating a significant effect on students at SMK Negeri 1 Kotabumi, North Lampung.